EFEKTIVITAS LUMPUR AKTIF DALAM MENURUNKAN NILAI BOD (Biological Oxygen Demand) DAN COD (Chemical Oxygen Demand) PADA LIMBAH CAIR UPT LAB. ANALITIK UNIVERSITAS UDAYANA - Rizkia Widyawati, Yudith; Putra Manuaba, Ida Bagus; Dwi Adhi Suastuti, Ni Gst Ayu Made (Jurnal Kimia (Journal of Chemistry); Vol. 9, no. 1 Januari 2015, 2015)
This research was conducted to determine the effectivity of activated sludge to decrease the Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) of waste water produced by the UPT. Lab Analitik Udayana University. This research used varied sediment masses and aeration times in order to determine the optimum conditions of activated sludge and the effectivity. Variation of the masses were 5, 10 and 20 grams and the aeration times were 1; 2; 3; 4 and 5 days. The result showed that both parameters studied decreased as a result of biological activity which oxidizes organic and inorganic compounds contained in the waste water. Five grams sediment within aeration time 4 days were the most optimum condition in decreasing the BOD  (up to 75,25 %)  and COD (up to 58,08 %). The results of One-way ANOVA showed there were a significant difference between BOD and COD before and after 3 , 4 and 5 days treatment.
Keywords: activated sludge, effectivity, BOD and COD, laboratory waste